Pembelajaran Berbasis Masalah sebagai Strategi Inovatif untuk Meningkatkan Hasil Belajar Biologi pada Materi Keanekaragaman Hayati - Pridi, Hironima; Ndukang, Sardina; Djalo, Aloysius; Missa, Hildegardis (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
Biology education, particularly in the topic of biodiversity, faces challenges in improving student learning outcomes. One effective approach is problem-based learning (PBL), which promotes active student involvement in solving real-world problems. This study examines the impact of PBL on Student Learning Outcomes in biodiversity at the high school level. A quasi-experimental design was conducted at SMA Negeri 5, involving two classes selected through purposive sampling: an experimental class using PBL and a control class taught using conventional methods. Learning outcomes were assessed via pretests, posttests, N-Gain analysis, and ANCOVA. The results showed a significant improvement in the experimental class. The average pretest score for the experimental class was 45.63, while the posttest score increased to 80.1, resulting in an N-Gain of 0.37 (moderate). In contrast, the control class had a pretest score of 45.31 and a posttest score of 75, with an N-Gain of 0.49. Despite the control class showing a slightly higher N-Gain, the PBL model was more effective in improving learning outcomes, with 93.75% of students in the experimental class achieving mastery compared to 65.63% in the control class. ANCOVA results revealed a p-score of 0.002, confirming that PBL significantly enhances student learning outcomes.